2006
DOI: 10.1016/j.exer.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure, localization and role in oxidative stress of methionine sulfoxide reductase A (MSRA) in the monkey retina

Abstract: MSRA (EC 1.8.4.6) is a member of the methionine sulfoxide reductase family that can reduce methionine sulfoxide (MetO) in proteins. This repair function has been shown to protect cells against oxidative damage. In this study we have assembled the complete gene structure of msrA and identified the presence of two distinct putative promoters that generate three different transcripts. These transcripts were cloned by 5'RACE and code for three MSRA isoforms with different N-termini. The different forms of MSRA tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 33 publications
8
62
0
Order By: Relevance
“…Although this possibility can not be ruled out, we do not believe that this condition contributes to the present data since similar effects have been observed upon deletion of MsrA in retinal cells which are not found in an anoxic environment (Lee et al, 2006). Moreover, no changes in ROS levels or mitochondrial membrane potential were seen in the mock transfected controls.…”
Section: Discussionsupporting
confidence: 48%
“…Although this possibility can not be ruled out, we do not believe that this condition contributes to the present data since similar effects have been observed upon deletion of MsrA in retinal cells which are not found in an anoxic environment (Lee et al, 2006). Moreover, no changes in ROS levels or mitochondrial membrane potential were seen in the mock transfected controls.…”
Section: Discussionsupporting
confidence: 48%
“…The hybridization signal is low, and becomes evident on the X-ray film only after the longer form MsrA bands are overexposed ( Figure 10A, thin arrow). There are also protein bands with molecular weights of ~46 and ~48 kD indicating homodimers of MsrA long form proteins ( Figure 10A, arrow head), even with protein samples thoroughly treated by reducing agents before SDS-PAGE, as has been reported by other laboratories [Lee et al, 2006]. On our films, there is also a band with a molecular weight of 39 kD, possibly heterodimers formed by a long form protein of MsrA (MW: 23 kD) and a smaller form of MsrA protein (MW 16 kD) ( Figure 10A, *).…”
Section: Evidence Of the Existence Of A Truncated Form Of Msra In Mousupporting
confidence: 52%
“…Currently, most studies on MsrA isoforms emphasize the 5' terminus where different isoforms for mitochondrial signal peptide are present and dictates where protein products are localized within the mitochondria [Kim & Gladyshev, 2006;Lee et al, 2006;Haenold et al, 2007]. There is evidence that transcripts of MsrA from alternative splicings at the 3' end of the MsrA gene are present in the mammalian EST database, however, no detailed studies on these transcripts have been reported [Kim & Gladyshev, 2006].…”
Section: Background and Overview Of Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations